2022
DOI: 10.1186/s12929-022-00868-1
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of sentinel lymph node microenvironment during tumor metastasis

Abstract: Metastasis is a major cause of death in patients with cancer. The two main routes for cancer cell dissemination are the blood and lymphatic systems. The underlying mechanism of hematogenous metastasis has been well characterized in the past few decades. However, our understanding of the molecular basis of lymphatic metastasis remains at a premature stage. Conceptually, cancer cells invade into lymphatic capillary, passively move to collecting lymphatic vessels, migrate into sentinel lymph node (SLN;, the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 161 publications
(184 reference statements)
0
14
0
Order By: Relevance
“…In addition to the tumor microenvironment, the immune status of lymph nodes in the tumor‐draining area and spleen are also tightly related to the antitumor effect, especially for post‐treatment tumor relapse and metastasis. [ 52 ] The results revealed that the maturation of DCs (CD11c + CD40 + , CD11c + MHCII + , and CD11c + CD80 + CD86 + ) in the tumor‐draining lymph nodes was significantly higher in the CpG@ M M ‐ P L ‐treated mice than those mice injected with saline and CpG alone ( Figure A–D and Figure S16, Supporting Information). Moreover, flow cytometry analysis of spleen single‐cell suspension demonstrated that CpG@ M M ‐ P L treatment relatively promoted the IFN‐ γ , TNF‐ α , granzyme B, and perforin generation of CD8 + T cells in the spleen compared to those in the saline and CpG groups, meaning the tumor‐killing functions of CTLs in the spleen were extremely elevated after administration of the nanoplatforms (Figure 6E–H).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the tumor microenvironment, the immune status of lymph nodes in the tumor‐draining area and spleen are also tightly related to the antitumor effect, especially for post‐treatment tumor relapse and metastasis. [ 52 ] The results revealed that the maturation of DCs (CD11c + CD40 + , CD11c + MHCII + , and CD11c + CD80 + CD86 + ) in the tumor‐draining lymph nodes was significantly higher in the CpG@ M M ‐ P L ‐treated mice than those mice injected with saline and CpG alone ( Figure A–D and Figure S16, Supporting Information). Moreover, flow cytometry analysis of spleen single‐cell suspension demonstrated that CpG@ M M ‐ P L treatment relatively promoted the IFN‐ γ , TNF‐ α , granzyme B, and perforin generation of CD8 + T cells in the spleen compared to those in the saline and CpG groups, meaning the tumor‐killing functions of CTLs in the spleen were extremely elevated after administration of the nanoplatforms (Figure 6E–H).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we summarize the biological functions and clinicopathological features of the aberrantly expressed circRNAs in ESCC (Table 1). ESCC mainly carries out distant metastasis through the lymphatic system, causing patients to lose the opportunity for early surgery, and is directly related to poor prognosis (118)(119)(120). High expression of circ_0048117, circ_0001093, circ_0000705, and circHIPK3 are closely related to lymph node metastasis and the TNM stage of ESCC (84, 88,90,95).…”
Section: Circrna Dysregulation Modulates the Clinical Characteristics...mentioning
confidence: 99%
“…[7,8] Therefore, it is of great significance to regulate the immune response of LN for and inhibit the spread of disease-causing organisms. [9,10] Nanomaterials are designed to load immune agonists, which could activate immune cells in lymph nodes to initiate an immune response. [11][12][13][14][15] However, several challenges remain in achieving spatiotemporal control of immune regulation of LN.…”
Section: Introductionmentioning
confidence: 99%
“…For example, sentinel LN are important metastasis pathway for cancer cells [7,8] . Therefore, it is of great significance to regulate the immune response of LN for and inhibit the spread of disease‐causing organisms [9,10] . Nanomaterials are designed to load immune agonists, which could activate immune cells in lymph nodes to initiate an immune response [11–15] .…”
Section: Introductionmentioning
confidence: 99%